Making Institutional Repositories Work - Callicott, Burton B.; Scherer, David; Wesolek, Andrew (USA Purdue University Press)
Quickly following what many expected to be a wholesale revolution in library practices, institutional repositories encountered unforeseen problems and a surprising lack of impact. Clunky or cumbersome interfaces, lack of perceived value and use by scholars, fear of copyright infringement, and the like tended to dampen excitement and adoption. This collection of essays, arranged in five thematic sections, is intended to take the pulse of institutional repositories$1 (Bto see how they have matured and what can be expected from them, as well as introduce what may be the future role of the institutional repository.s
English
Keywords: Information Science; Institutional repository; Open access; Scholarly communication; Thesis